2022
DOI: 10.3390/ijerph19095574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Inpatient Psychiatric Mother-Baby Unit Using a Patient Reported Experience and Outcome Measure

Abstract: Understanding the patient experience of admission to a psychiatric mother-baby unit (MBU) informs service improvement and strengthens patient-centered care. This study aims to examine patients’ experience, satisfaction, and change in mental health status related to MBU admission. At discharge, 70 women admitted to a public MBU completed the Patient Outcome and Experience Measure (POEM), rated the usefulness of therapeutic groups, and provided written qualitative feedback. Paired sample t-tests, correlations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The Lavender MBU is an acute mental health inpatient service that provides specialist perinatal assessment and treatment for women with significant mental health difficulties that cannot be managed in the community and their baby(s) [ 18 ]. Women eligible for admission require inpatient treatment for a mental health condition that cannot be managed in the community, have an infant under 12 months old, reside in Queensland (Australia), and are not homeless or at risk of homelessness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lavender MBU is an acute mental health inpatient service that provides specialist perinatal assessment and treatment for women with significant mental health difficulties that cannot be managed in the community and their baby(s) [ 18 ]. Women eligible for admission require inpatient treatment for a mental health condition that cannot be managed in the community, have an infant under 12 months old, reside in Queensland (Australia), and are not homeless or at risk of homelessness.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research comparing MBUs to general psychiatric wards found that patients and staff preferred the MBU, describing superior facilities, treatment, and holistic, perinatally-focused support [ 17 ]. Australian patients evaluating their experiences gave overwhelmingly positive feedback, reporting improvements in parenting knowledge and confidence, and a positive change in their own mental health status [ 18 ]. Evaluations of MBUs in several countries displayed strong evidence for their effectiveness in treating maternal mental health, while also identifying improved health and relationships for the co-admitted infants [ 2 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-and post-natal psychiatric illness is a signi cant global health issue, affecting around 20% of women while remaining largely underdiagnosed and undertreated [2][3][4][5]. An estimated one in ve women will experience postnatal depression or anxiety in the rst year after the birth of their child [2,6,7]. Approximately one in 10 women will experience clinically signi cant symptoms of depression during pregnancy [6].…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%